SARS-CoV-2 Spike Protein Suppresses ACE2 and Type I Interferon Expression in Primary Cells From Macaque Lung Bronchoalveolar Lavage - Sui, Yongjun; Li, Jianping; Venzon, David J.; Berzofsky, Jay A. (Frontiers in Immunology, 2021)
SARS-CoV-2 virus causes upper and lower respiratory diseases including pneumonia, and in some cases, leads to lethal pulmonary failure. Angiotensin converting enzyme-2 (ACE2), the receptor for cellular entry of SARS-CoV-2 virus, has been shown to protect against severe acute lung failure. Here, we provide evidence that SARS-CoV-2 spike protein S1 reduced the mRNA expression of ACE2 and type I interferons in primary cells of lung bronchoalveolar lavage (BAL) from naïve rhesus macaques. The expression levels of ACE2 and type I interferons were also found to be correlated with each other, consistent with the recent finding that ACE2 is an interferon-inducible gene. Furthermore, induction of ACE2 and type I interferons by poly I:C, an interferon inducer, was suppressed by S1 protein in primary cells of BAL. These observations suggest that the downregulation of ACE2 and type I interferons induced by S1 protein may directly contribute to SARS-CoV-2-associated lung diseases.